Syndecan-1 mediates sorting of soluble lipoprotein lipase with sphingomyelin-rich membrane in the Golgi apparatus - Sundberg, Emma L. (Dev Cell, 2019)
In the secretory pathway, budding of vesicular transport carriers from the trans Golgi network (TGN) must coordinate specification of lipid composition with selection of secreted proteins. We elucidate a mechanism of soluble protein cargo sorting into secretory vesicles with a sphingomyelin rich membrane; the integral membrane proteoglycan Syndecan-1 (SDC1) acts as a sorting receptor, capturing the soluble enzyme Lipoprotein Lipase (LPL) during export from the TGN. Sorting of LPL requires bivalent interactions between LPL and SDC1-linked heparan sulfate chains and between LPL and Golgi membrane. Physical features of the SDC1 transmembrane domain, rather than specific sequence, confer targeting of SDC1 and bound LPL into the sphingomyelin secretion pathway. This study establishes that physicochemical properties of a protein transmembrane domain that drive lateral heterogeneity of the plasma membrane, also operate at the TGN to confer sorting of an integral membrane protein and its ligand within the biosynthetic secretory pathway.